Designing with community health workers in Latin America - Espinoza,F; Re,MD; Calvo,RA (Interactions, 2024)
Community + Culture features practitioner perspectives on designing technologies for and with communities. We highlight compelling projects and provocative points of view that speak to both community technology practice and the interaction design field as a whole.